CONCERNS IN QUALITATIVE RESEARCH AND NURSING SCIENCE - Joko Gunawan; Nur Asni Wahab; Elmiati Elmiati (Belitung Raya Foundation, Indonesia, 2015)
Qualitative research methods become increasingly popular in nursing. However, most of nursing students have argued and debated about issues and meanings of the qualitative research in nursing science. This article is noted to discuss the qualitative aspects and concerns.